HUBUNGAN TINGKAT PENGETAHUAN PASIEN TENTANG PENGELOLAAN PENYAKIT DENGAN KESIAPAN MENGHADAPI SERANGAN BERULANG PADA ASMA BRONKIAL DI WILAYAH KERJA PUSKESMAS PARIAMAN - Mechi Silvia Dora (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2022)
Asthma is a chronic inflammatory process of the respiratory tract which involves many cells and their elements. The prevalence of asthma according to the World Health Organization (WHO) in 2016 is around 235 million with a mortality rate of more than 80% in developing countries. At the Pariaman City Health Office it was found that of the 7 puskesmas in Pariaman city where the Pariaman puskesmas had the most asthma in 2021. The purpose of this study was to determine the relationship between the level of patient knowledge about disease management and readiness for recurrent attacks of bronchial asthma in the region. pariaman health center work. This type of descriptive analytic research with the research design used was cross sectional, this research was conducted in the working area of ​​the Pariaman Health Center, sampling was carried out using a porposive sampling technique with a sample size of 35 respondents. The data collection tool was carried out using a questionnaire, this statistical analysis used the chi-square test. The results showed that more than half of the respondents (54.3%) had poor knowledge about the management of bronchial asthma, almost half of the respondents (48.6%) were less prepared to deal with recurrent attacks of bronchial asthma, and there was a significant relationship between knowledge and readiness in dealing with recurrent attacks of bronchial asthma (p value = 0.000 <0.05). Knowledge greatly influences readiness for recurrent attacks of bronchial asthma, patients should further increase their knowledge of how to manage bronchial asthma, and in future researchers about the problem of asthma and be able to examine other factors that are more influential in managing asthma attacks. bronchial.